Financial Crisis, Economic Recovery, and Banking Development in Russia, and other FSU Countries - Haizhou Huang; Dalia Marin; Chenggang Xu (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2004)
This paper provides a unified analysis for the onset of the 1998 financial crisis and the strong economic recovery afterward in Russia and other former Soviet Union countries. Before the crisis a banking failure arose owing to the coexistence of a lemons credit market and high government borrowing. In a lemons credit market low credit risk firms switched from bank to nonbank finance, including trade credits and barter trade, generating an externality on banks' interest rates. The collapse of the treasury bills market in the financial crisis triggered a change in banks' lending behavior, providing initial conditions for banking development.
urn:nbn:de:bvb:19-epub-13472-0
Keywords: G3; G21; P34; O16; D82; 330; banking development; institutional trap; financial crisis